Why Invest in ICTs for agriculture? - Tetteh Kwasi Nuer, Alexander; Agbeko, Daniel; Worlali, Senyo; Mwangi Thiga, Moses; Ndogo Ndung'u, Simon; Wangari Mutiga, Mary; Babcock, Lee H. (Technical Centre for Agricultural and Rural Cooperation, 2018)
With the ability to reach many farmers with timely and accessible content, the use of information and communication technologies (ICTs) for agriculture (ICT4Ag) has the potential to transform farming and food production, worldwide. ICT4Ag supports new methods in the monitoring and management of soils, plants and livestock (precision agriculture), access to online markets, and improved communication between value chain stakeholders, among others. The services provided are vital in connecting farmers with the information they need to improve their agricultural productivity and reduce poverty. Through case studies and examples of ICT4Ag initiatives from across Asia, the Caribbean and sub-Saharan Africa, the first chapter looks at how ICT4Ag actually works to drive economic development across developing economies.